An integrated component based knowledge management (KM) model for health sector organizations in Punjab, Pakistan - Arshad, Arfan (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2020)
In the present age, a competent and efficient KM system supports the KM activities while improving and maintaining the overall performance and provision of quality service. Therefore, KM in healthcare organizations helps healthcare workers and professionals to keep updated with current and latest medical knowledge. Pakistan is among those progressing nations in which the significance of knowledge management regarding healthcare services has been realized and acknowledged, but its practices appear to be unsuccessful in gaining sufficient awareness. Though KM is turning out to be a recognized discipline which has been established along with various supporting applications and techniques in the last two decades or so, its adoption and implementation in healthcare domain seems to be challenging. Current studies have revealed that the lack of systematic procedures for the development and application of KMS activities appear to be a major challenge for successful KM implementation in healthcare organizations of Pakistan. This study emphasizes on investigating and evaluation of the use of information technology and its existing state to support knowledge management functions in public-sector healthcare organizations of Pakistan. Furthermore, the purpose of this research and study is to explore, examine and evaluate the significant factors that influence the successful implementation of KMS and success of KM practices in the public-sector healthcare organizations of Pakistan. Moreover, the current study and research also investigate and analyzes the existing KM models and propose an integrated component-based knowledge management model to fill the gaps and deficiencies of current models used (if any), in the healthcare industry in Pakistan. The research is suggestively supported by the past studies to investigate KM implementation and application activities and help at evaluating the applicability and soundness of the proposed KM model and how it can be utilized to enhance the performance of KMS in public-sector healthcare organizations of Pakistan. The present research applied a triangulation mixed method approach to investigate the existing state of KM in healthcare systems, its maturity level, and an overall understanding of the knowledge management concept by the professionals related to public-sector healthcare organizations in Pakistan. Based upon the quantitative and qualitative results analysis, the proposed integrated component-based KM model comprising of a four-layered architecture was developed, enhanced and improved in three phases. In the first phase, the conceptual model was developed based upon the hypothesis, followed by the development of an empirical model in the second phase that was statistically tested and assessed for significance and model fit in the form of measurement model and structural model by using SPSS and PLS-SEM (Partial least square-structured equation modeling). The statistical results exhibited that, all the specified research hypotheses appeared to be significantly valid except the two, i.e., “impact of exogenous factors on KM specifications” and “impact of KM success on overall organizational performance” appeared to be weak and non-significant. Furthermore, the empirical model was converted into an integrated component-based KM model demonstrating the functional components of the proposed model and the relationships among them. Last but not least, the case healthcare organizations appear to exhibit a sound IT infrastructure to support KM activities but lack successful KM implementation due to significant influential factors such as lack of top management leadership, lack of funds, lack of understanding the KM potential benefits, lack of resources, and organizational and social culture.